ANALISIS KINERJA KEUANGAN MELALUI PENDEKATAN RASIO KEUANGAN SEBAGAI DASAR PENGAMBILAN KEPUTUSAN MANAJERIAL PADA PT AMARI OPHELOS LARUNDA INDONESIA PERIODE 2021–2024 - Jesicha Angreini Slamet; Risa Watti (CV. Denasya Smart Publisher, 2025)
Financial performance evaluation is an important aspect in determining the sustainability and effectiveness of a company's operational activities. This study aims to analyze the financial performance of PT Amari Ophelos Larunda Indonesia during the 2021–2024 period using financial ratio analysis as a basis for managerial decision-making. The research employed a quantitative descriptive approach utilizing secondary data obtained from the company's financial statements, including balance sheets and income statements. The analysis consisted of liquidity ratios represented by Current Ratio and Quick Ratio, solvency ratios represented by Debt to Asset Ratio and Debt to Equity Ratio, activity ratios represented by Inventory Turnover and Total Asset Turnover, and profitability ratios represented by Net Profit Margin and Return on Assets. The findings indicate that the company's liquidity level remained relatively adequate in fulfilling short-term obligations despite fluctuations throughout the observation period. Solvency ratios suggest that the company maintained a manageable level of debt financing. Activity ratios reveal that asset utilization was not fully optimized, while profitability ratios demonstrate fluctuations in the company's ability to generate profits. Overall, the financial performance of PT Amari Ophelos Larunda Indonesia during 2021–2024 can be categorized as fairly good, although improvements in asset management efficiency and profitability are still required to support sustainable business growth and managerial decision-making.